Pola internalisasi nilai-nilai moderasi beragama di SMAI Diponegoro Wagir - Listiyani, Novida (Maliki Interdisciplinary Journal, 2024)
The Indonesian nation is known for its diversity, it is not surprising that there needs to be an attitude of caution or tolerance in living together as good Indonesian citizens. However, in fact, in Malang City there are still cases of radicalism and liberalism, especially among students in Islamic educational institutions. So, researchers want to examine the process of internalizing the values ​​of religious moderation in Islamic educational institutions, namely SMAI Diponegoro Wagir. Based on observations made by researchers, there is a strong condition of religious tolerance in the school. The aim of this research is to know and understand the pattern of religious moderation in the process of internalizing the values ​​of religious moderation at SMAI Diponegoro Wagir. This research uses a qualitative approach with a case study type. The research object is SMAI Diponegoro Wagir. The techniques used to collect data are through observation, interviews and documentation. In selecting the sample, the researcher used a purposive sampling technique. Then for the process of analyzing data through data collection, data reduction, data analysis, and drawing conclusions. The results of this research indicate that the process of internalizing the values ​​of religious moderation at SMAI Diponegoro Wagir can be carried out through religious moderation patterns and approaches. The pattern of religious moderation can be seen from internal and external levels of the school.